Consumerism in Kurdish Society in the Thought of Jean Baudrillard (Raparin Journal of Humanities (RJH), 2024)
Consumerism is subject targeting by the object and the marketplace in which the subject itself is the producer of the goods but it is deeply affected by the high pressure of the spectacles represented in the Post-Industrial society, i.e., the dreams of the subject itself, are limited to having goods, purchases and expenditures. This is, in fact, not related to one of the uses of the goods themselves, but to several other codes. Thus, the goods have been given an effective role to the extent that they contribute to giving the individuals’ social status and identity so that everyone, from all corners of the world, make an attempt to do the expenditure with the goods. According to Baudrillard, due to the influence of the codes and trademarks, society has become passive and has surrendered to the goods. In this case, the consumers will lose the demand for purchase as the modes and the trademarks are increasing and are temporary on one hand, and not everyone is able to afford the purchases. This results in dissatisfaction rather than satisfaction. Therefore, the worriedness of not being able to purchase the goods is one of the obvious characteristics of the consumerism society, and this has resulted in a shift in which the subject has been turned into the target of the object. The goods are directing the individuals towards their demands and the satisfaction of the subject is linked to the amount of having the goods. The Kurdish society has been rapidly and unconsciously moving towards consumerism in the last two decades, on the grounds of the Internet and technology. This is shown in the form of transforming the Kurdish subjects into a world of privilege. Hence, our aim of the study is to reveal the consumerism in our society and to examine its basics.